Cost of childhood acute otitis media in primary care in the Netherlands: economic analysis alongside a cluster randomised controlled trial - Rick T. van Uum; Roderick P. Venekamp; Clémence T. B. Pasmans; G. Ardine de Wit; Alies Sjoukes; Alma C. van der Pol; Roger A. M. J. Damoiseaux; Anne G. M. Schilder (BMC, 2021)
Abstract Background Acute otitis media (AOM) is among the most common paediatric conditions managed in primary care. Most recent estimates of the cost of AOM date from a decade ago and lack a full societal perspective. We therefore explored the societal cost of childhood AOM in the Netherlands within the setting of a trial comparing the effectiveness of an intervention aimed at educating general practitioners (GPs) about pain management in AOM compared to usual care. Methods Economic analysis alongside a cluster randomised controlled trial conducted between February 2015 and May 2018 in 37 practices (94 GPs). In total, 224 children with AOM were included of which 223 (99%) completed the trial (intervention: n = 94; control: n = 129). The cost of AOM due to health care costs, patient and family costs, and productivity losses by parent caregivers were retrieved from study diaries and primary care electronic health records, during 28-day follow-up. We calculated mean cost (€ and $) per AOM episode per patient with standard deviations (SD, in €) regardless of study group assignment because there was no clinical effect of the trial intervention. In sensitivity analysis, we calculated cost in the intervention and usual care group, after exclusion of extreme outliers. Results Mean total AOM cost per patient were €565.93 or $638.78 (SD €1071.01); nearly 90% of these costs were due to productivity losses experienced by parents. After exclusion of outliers, AOM cost was €526.70 or $594.50 (SD €987.96) and similar in the intervention and usual care groups: €516.10 or $582.53 (SD €949.69) and €534.55 or $603.36 (SD €920.55) respectively. Conclusions At €566 or $639 per episode, societal cost of AOM is higher than previously known and mainly driven by productivity losses by children's parents. Considering its high incidence, AOM poses a significant economic burden that extends beyond direct medical costs. Trial registration Netherlands Trial Register no. NTR4920: http://www.trialregister.nl/trialreg/admin/rctview.asp?TC=4920 .